2013
DOI: 10.1539/joh.12-0034-oa
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Work Hours and Actual Availability of Weekly Rest Days with Cardiovascular Risk Factors

Abstract: Associations of Work Hours and Actual Availability of Weekly Rest Days with Cardiovascular Risk Factors: Osamu ITANI, et al. Division of Public Health, Department of Social Medicine, Nihon University School of Medicine— Objectives The aim of study was to determine the associations of work hours and actual availability of weekly rest days with the onset of lifestyle‐related diseases such as obesity, hypertension, hypertriglyceridemia, low levels of high‐density lipoprotein (HDL) cholesterol and hyperglycemia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…A recent study in Japan showed no association between working hours and hypertension risk (Itani et al, 2013). In contrast, another Japanese study showed that DBP but not SBP was positively associated with working hours in assembly-line workers and no significant association of SBP and DBP with working hours in clerks or engineers/special technicians (Nakamura et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study in Japan showed no association between working hours and hypertension risk (Itani et al, 2013). In contrast, another Japanese study showed that DBP but not SBP was positively associated with working hours in assembly-line workers and no significant association of SBP and DBP with working hours in clerks or engineers/special technicians (Nakamura et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, Nakamura et al (2012), Artazcoz et al (2009) andYang et al (2006) found a positive linear relationship in overall subjects or some sub-groups, whereas Itani et al (2013) and Pimenta et al (2009) showed no significant relationship, and Wada et al (2006) and Nakanishi et al (2001) reported an inverse relationship. These studies have limitations in their design.…”
Section: Introductionmentioning
confidence: 84%
“…Itani et al (24) reported that working in shifts was responsible for a rise of up to 40% in the incidence of CVD among their study population. In our study, 10% of the studied samples never exercised and only 37% exercised between once and 5 times a week or more.…”
Section: Discussionmentioning
confidence: 92%
“…A cross-sectional study on the association between daily working hours and metabolic syndrome in male Japanese workers reported significant outcome in subjects aged 40 or more, but, no significant association was observed between working hours and prevalence of metabolic syndrome when stratified by age [12]. However, a longitudinal study conducted for male workers in local public institutions of Japan suggested that long working hours increase the onset risk of hypertriglycemia [19]. In addition, a recent study conducted for Korean adults [5] demonstrated that long working hours are significantly related to risk of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%